2021
DOI: 10.3390/nano11123339
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Inverse Design of Structural Colors of Nanoparticle Systems via Deep Neural Network

Abstract: Noniridescent and nonfading structural colors generated from metallic and dielectric nanoparticles with extraordinary optical properties hold great promise in applications such as image display, color printing, and information security. Yet, due to the strong wavelength dependence of optical constants and the radiation pattern, it is difficult and time-consuming to design nanoparticles with the desired hue, saturation, and brightness. Herein, we combined the Monte Carlo and Mie scattering simulations and a bid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Finally, the color spectrum observed in AlxOy-coated CFFs shares a conceptual link with the structural colors of gold nanoparticle systems described by Ma et al [32], i.e., the size of the particles profoundly affects the scattering and absorption of light, with larger particles exhibiting shifts in resonance peaks and stronger scattering, leading to a spectrum of observed colors from red to purple as particle size increases. Just as the colors in nanoparticle systems are shaped by factors like particle size, volume fraction, and layer thickness, the hues seen in AlxOy-coated fabrics result from alterations in film granularity and thickness due to varying ALD cycles.…”
Section: Thermal Analysis Of the Al X O Y -Coated Cffsupporting
confidence: 69%
“…Finally, the color spectrum observed in AlxOy-coated CFFs shares a conceptual link with the structural colors of gold nanoparticle systems described by Ma et al [32], i.e., the size of the particles profoundly affects the scattering and absorption of light, with larger particles exhibiting shifts in resonance peaks and stronger scattering, leading to a spectrum of observed colors from red to purple as particle size increases. Just as the colors in nanoparticle systems are shaped by factors like particle size, volume fraction, and layer thickness, the hues seen in AlxOy-coated fabrics result from alterations in film granularity and thickness due to varying ALD cycles.…”
Section: Thermal Analysis Of the Al X O Y -Coated Cffsupporting
confidence: 69%
“…The phenomenon of radiative (light) transfer in nanoparticle systems is ubiquitous and plays a vital role in numerous applications, including climate science, ocean optics, remote sensing, biomedicine, color paints, solar energy utilization and radiative cooling [1][2][3][4][5][6][7][8][9][10][11][12]. Accurate prediction of the radiative properties of nanoparticle systems is central to such applications.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the unprecedented development of machine learning has made it a powerful tool for solving complex computing and inverse design problems. Several studies have reported machine learning methods to facilitate the design of structural colors and inverse design of nanostructures and materials to achieve the desired optical response [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. So et al [ 28 ] achieved the simultaneous inverse design of materials and structural parameters of core–shell nanoparticles by using neural networks.…”
Section: Introductionmentioning
confidence: 99%